Influence of gender on preferred dance style of Filipino street dancers - Segala, Hanna Mae Danniela R. 2000-
The purpose of this study is to explore the factors influencing the preferred dance style of Filipino street dancers and examine the role of gender in their preferred dance style. The objective is to find out what dance styles Filipino street dancers prefer, what factors influence their choices, and analyze the role of gender in their preferred dance style. The participants of this study were 10 Filipino street dancers who had adequate experience in street dance. A semi-structured interview was conducted to gather the data and thematic analysis was used to interpret the findings. The results of this study revealed that preferred dance styles were influenced by Musical Influence, Builds Confidence, Strength in Footwork, Way of Expression, and Gender Preference. Findings reveal that while gender did influence the preferred dance styles of some Filipino street dancers, it was not the primary factor in their choice of style. Gender preference aligns with Butler’s Gender Performativity Theory, showing that gender is performed in personal and diverse ways through dance and that performing gender is not limited to what you are. By highlighting the experiences of dancers with diverse gender identities, it aims to challenge stereotypes, promote inclusion, and support identity formation and expression within the dance community.